Some Permanent Magnet Synchronous Motor (PMSM) Sensorless Control Methods based on Operation Speed Area - Harini, Bernadeta Wuri (Universitas Ahmad Dahlan, 2021)
This paper compares some sensorless Permanent Magnet Synchronous Motor (PMSM) controls for driving an electric vehicle in terms of operating speed. Sensorless control is a type of control method in which sensors, such as speed and position sensors, are not used to measure controlled variables.Â The controlled variable value is estimated from the stator current measurement. Sensorless control performance is not as good as a sensor-based system. This paper aims are to recommend a control method for the PMSM sensorless controls that would be used to drive an electric vehicle. The methods that we will discuss are divided into four categories based on the operation speed area.Â They are a startup, low speed, high speed, and low and high-speed areas. The low and high-speed area will be divided into with and without switching.Â If PMSM more work at high speed, the most speed area that is used, we prefer to choose the method that works at high speed, that is, the modification or combination of two or more conventional methods.